Comparison Analysis Of Murabahah And Mudharabah Financing Risk Management From Sharia Micro-Finance Institutions - Hamidah, Raisa Aribatul; Alam, Azhar; Izzuddin, Azzam (Jurnal Ar-Ribh, 2022)
This study aims to reveal the phenomenon in the field about the description of the comparison of risk management strategies between murabahah financing and mudharabah financing from the BMT side. This study uses descriptive qualitative research methods, through data collection methods in the form of interviews. The researcher interviewed 9 respondents who have experience in dealing with the risks of murabahah financing and mudharabah financing at BMT. This study shows risk mitigation efforts so that risks do not occur in both contracts, namely BMT tightens the selection stage because in both contracts BMT must measure the level of business risk of its members in calculating profits or in returning funds so as not to have the opportunity to harm both parties and the financial statements must also be transparent. This study also suggests that in murabahah financing and mudharabah financing, BMT must strictly apply the precautionary and appropriate principles to maintain institutional health in order to minimize the risks that occur. This research is expected to be a reference for BMT in terms of innovative strategies to overcome the risks of mudharabah and murabahah financingRisk Management, Murabaha Financing, Mudhrabah Financing, Islamic Microfinance Institutions (BMT)